Exercise training modulates glutamic acid decarboxylase-65/67 expression through TrkB signaling to ameliorate neuropathic pain in rats with spinal cord injury. (May 2020) - Li, Xiangzhe; Wang, Qinghua; Ding, Jie; Wang, Sheng; Dong, Chuanming; Wu, Qinfeng
Neuropathic pain is one of the most frequently stated complications after spinal cord injury. In post-spinal cord injury, the decrease of gamma aminobutyric acid synthesis within the distal spinal cord is one of the main causes of neuropathic pain. The predominant research question of this study was whether exercise training may promote the expression of glutamic acid decarboxylase-65 and glutamic acid decarboxylase-67, which are key enzymes of gamma aminobutyric acid synthesis, within the distal spinal cord through tropomyosin-related kinase B signaling, as its synthesis assists to relieve neuropathic pain after spinal cord injury. Animal experiment was conducted, and all rats were allocated into five groups: Sham group, SCI/PBS group, SCI-TT/PBS group, SCI/tropomyosin-related kinase B-IgG group, and SCI-TT/tropomyosin-related kinase B-IgG group, and then T10 contusion SCI model was performed as well as the tropomyosin-related kinase B-IgG was used to block the tropomyosin-related kinase B activation. Mechanical withdrawal thresholds and thermal withdrawal latencies were used for assessing pain-related behaviors. Western blot analysis was used to detect the expression of brain-derived neurotrophic factor, tropomyosin-related kinase B, CREB, p-REB, glutamic acid decarboxylase-65, and glutamic acid decarboxylase-67 within the distal spinal cord. Immunohistochemistry was used to analyze the distribution of CREB, p-CREB, glutamic acid decarboxylase-65, and glutamic acid decarboxylase-67 within the distal spinal cord dorsal horn. The results showed that exercise training could significantly mitigate the mechanical allodynia and thermal hyperalgesia in post-spinal cord injury and increase the synthesis of brain-derived neurotrophic factor, tropomyosin-related kinase B, CREB, p-CREB, glutamic acid decarboxylase-65, and glutamic acid decarboxylase-67 within the distal spinal cord. After the tropomyosin-related kinase B signaling was blocked, the analgesic effect of exercise training was inhibited, and in the SCI-TT/tropomyosin-related kinase B-IgG group, the synthesis of CREB, p-CREB, glutamic acid decarboxylase-65, and glutamic acid decarboxylase-67 within the distal spinal cord were also significantly reduced compared with the SCI-TT/PBS group. This study shows that exercise training may increase the glutamic acid decarboxylase-65 and glutamic acid decarboxylase-67 expression within the spinal cord dorsal horn through the tropomyosin-related kinase B signaling, and this mechanism may play a vital role in relieving the neuropathic pain of rats caused by incomplete SCI.